Validation of the animal naming test for diagnosing minimal hepatic encephalopathy - A.D. Cano-Contreras; J.A. Velarde-Ruiz Velasco; F. Higuera-de-la-Tijera; C.F. Castillo-Diaz; D. Grajales-Velázquez; I. Méndez-Ruiz; V.A. Jiménez-Hernández; R. Aguirre-Lázaro; J.A. Sánchez-Hernández; H.R. Ordaz-Álvarez; J.M. Remes-Troche (Revista de Gastroenterología de México (English Edition))
Introduction and aim: The diagnosis of minimal hepatic encephalopathy (MHE) is complex in clinical practice, given that its adequate evaluation is time-consuming. The animal naming test (ANT1) has proven to be a useful tool for rapid MHE identification. Our aim was to validate the ANT1 in a cohort of Mexican patients with cirrhosis of the liver. Material and methods: An observational, cross-sectional, and analytic study was conducted within the time frame of June 2022 and May 2023. MHE diagnosis was made using the psychometric hepatic encephalopathy score (PHES). Patients with overt HE evaluated through the West Haven criteria were excluded. The ANT1 was performed on all participants. Results: A total of 199 patients with cirrhosis and 31 non-cirrhotic control subjects were analyzed. Women predominated (61.8% and 71%) and mean patient age was 55 ± 10 and 53.6 ± 12 (range 19–84 years), respectively. Ninety patients (45.2%) met the MHE criteria determined by the PHES. Using an ANT1 cutoff point of ≤15, MHE was identified in 65 (32.7%) patients, along with 75% sensitivity, 72% specificity, 53% positive predictive value, 87% negative predictive value, and 73% diagnostic accuracy. The area under the curve for diagnosing MHE was 0.763 (standard error, 0.081; 95% confidence interval, 0.604−0.923; p ≤ 0.0001). Conclusions: The ANT1 was shown to be a useful tool for identifying MHE in daily clinical practice. In our population, a cutoff point ≤15 animals named could be utilized for rapid screening of patients at high risk for progressing to overt HE, who would then require extensive testing. Resumen: Introducción: El diagnóstico de encefalopatía hepática mínima (EHM) es complejo en la práctica clínica ya que requiere invertir mucho tiempo para su adecuada evaluación. La prueba de denominación de animales (ANT1, siglas en inglés) ha demostrado ser una herramienta útil y rápida para la identificación de la EHM. Objetivo: Validar la prueba ANT1 en una cohorte de pacientes mexicanos con cirrosis hepática. Material y métodos: Estudio observacional, transversal y analítico realizado durante el periodo junio de 2022 a mayo de 2023. El diagnóstico de EHM se realizó con el puntaje psicométrico de encefalopatía hepática (PHES, siglas en inglés), se excluyeron pacientes con EH manifiesta evaluada con criterios de West Haven. Se realizó prueba ANT1 en todos los participantes. Resultados: Se analizaron 199 pacientes con cirrosis y 31sujetos en grupo control sin cirrosis, con predominio de mujeres (61.8% y 71%), edad 55 ± 10 y 53.6 ± 12 (rango 19 a 84 años). Noventa pacientes (45.2%) cumplieron criterios para EHM por PHES. Considerando ANT1 con punto de corte ≤15 se identificó EHM en 65 (32.7%) pacientes, así como sensibilidad de 75%, especificidad 72%, valor predictivo positivo 53%, valor predictivo negativo 87% y precisión diagnóstica 73%. El área bajo la curva para el diagnóstico de EHM fue 0.763 (error estándar de 0.081, intervalo de confianza del 95%, 0.604−0.923, p ≤ 0.0001). Conclusiones: La prueba ANT1 demostró ser una herramienta útil para la identificación de EHM en la práctica clínica diaria. En nuestra población el punto de corte ≤15 animales podría ser utilizado para el escrutinio rápido de pacientes con alto riesgo de progresión a EH manifiesta que requiera someterse a pruebas exhaustivas.